2016
DOI: 10.18632/oncotarget.13389
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide-periplocymarin conjugate prodrug for improving targetability and anti-tumor efficiency: synthesis, in vitro and in vivo evaluation

Abstract: Cardiac glycosides could increase intracellular Ca2+ ion by inhibiting the Na+/K+ATPase to induce apoptosis in many tumor cells. However, narrow therapeutic index, poor tumor selectivity and severe cardiovascular toxicity hinder their applications in cancer treatment. To improve the safety profile and tumor targetablility of cardiac glycosides, we designed octreotide conjugated periplocymarin, a cardiac glycoside isolated from Cortex periplocae. The conjugate showed higher cytotoxicity on MCF-7 cells and HepG2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
3
14
0
Order By: Relevance
“…6). Moreover, the FTIR studies showed no interaction between the CTX, OCT, and alginate, which was consistent with other results that used FTIR to confirm the physical interaction of all components but found no interaction between CTX, OCT and alginate 32,36 .…”
Section: Octreotide (Oct) Cetuximab (Ctx)supporting
confidence: 91%
See 2 more Smart Citations
“…6). Moreover, the FTIR studies showed no interaction between the CTX, OCT, and alginate, which was consistent with other results that used FTIR to confirm the physical interaction of all components but found no interaction between CTX, OCT and alginate 32,36 .…”
Section: Octreotide (Oct) Cetuximab (Ctx)supporting
confidence: 91%
“…Moreover, CTX was measured spectrophotometrically at a wavelength of 360 nm, while OCT was measured at 291 nm. It was previously reported that the CTX absorbance could be measured using a multiwall scanning spectrophotometer at 440 nm 31 , while OCT could be detected at 220 nm 32 . The variance between the published wavelength and our method could be due to the difference in the type of instruments used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we employed periplocymarin, a monomer component extracted from Periplocae Cortex. Currently, there are few studies on periplocymarin, most of which focus on its antitumor effects, while its role in cardiovascular disease remains largely unknown (Shiferaw et al, 2003;Zhang et al, 2016). The present study showed that acute administration of periplocymarin facilitated the cardiac function, resulting in an increase of MAP in mice.…”
Section: Discussionsupporting
confidence: 47%
“…In radiation oncology, this conjugate was more cytotoxic to MCF-7 and HepG2 tumor cells, but less cytotoxic to L-02 non-tumor cells. Tissue distribution of the conjugate using the H22 tumor model in mice resulted in a greater accumulation in tumors and a lower distribution in heart and liver compared to periplocymarin ( 15 ) alone [ 89 ]. Another study that sought to improve the delivery of CGs to reduce cardiotoxicity was performed with acetylthevetin B ( 16 ), isolated from the seeds of Thevetia peruviana (Pers), which showed potent in vitro cytotoxic activity.…”
Section: Future Perspectives and Conclusionmentioning
confidence: 99%